2011
DOI: 10.2485/jhtb.20.289
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Observation of HSP27 in Ameloblastomas

Abstract: We examined expression of Heat Shock Protein 27 (HSP27) molecules, in 10 cases of typical solid/ multicystic ameloblastoma, by means of immunohistochemistry. In general, HSP27 and pHSP27 positive staining products were frequently detected in the cytoplasms of the neoplastic cells. The expression pattern and/or strength are slightly different according to the cytological features of ameloblastomas. The immunohistochemical staining results suggest that the expression of HSP27 and pHSP27 is considered to be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…2, 3. Search of literatures revealed no other studies on HSPs in ameloblastoma with exception of two studies 4,5. The one revealed that HSP27 localized in human tooth germ is essential in cell growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, 3. Search of literatures revealed no other studies on HSPs in ameloblastoma with exception of two studies 4,5. The one revealed that HSP27 localized in human tooth germ is essential in cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the expression of HSP27 in ameloblastoma suggested its essential role in tumor development 4. The later, the localization and differential expressions of HSP27 and phosphorylated HSP27 (pHSP27) in histopathological subtypes of ameloblastoma were investigated suggesting the role of HSP27 in the differentiation of tumor cells 5. However, since the results were based on a limited number of specimens, new a large number of cases were added to previous cases stained with HSP27/pHSP27.…”
Section: Introductionmentioning
confidence: 99%
“…Also the expression of Hsp27 in ameloblastoma in his study was attributed towards tumor development. Fujita M, et al emphasize the role of Hsp 27 in differentiation of tumor cells after observing the localization and differential expressions in histopathological subtypes of ameloblastoma [109,110].…”
Section: Role In Infectionmentioning
confidence: 99%